2023
DOI: 10.1097/ftd.0000000000001147
|View full text |Cite
|
Sign up to set email alerts
|

A Population Pharmacokinetic Model to Predict the Individual Starting Dose of Tacrolimus for Tunisian Adults after Renal Transplantation

Amani Abderahmene,
Marith I. Francke,
Louise M. Andrews
et al.

Abstract: Background: Tacrolimus is the most frequently used immunosuppressive drug for preventing renal rejection. However, its use is hampered by its narrow therapeutic index and large intra and interpatient variability in pharmacokinetics. The objective of this study was to externally validate a tacrolimus population pharmacokinetic model developed for the Dutch population and adjust the model for the Tunisian population for use in predicting the starting dose requirement after kidney transplantation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…14 Patients with CYP3A5-expressing genotypes require 1.5 to 2 times the dose of tacrolimus to achieve the same blood concentration. [15][16][17][18] The tacrolimus analysis of the subjects in this study who received the same dose showed that the AUC values of the CYP3A5-nonexpressing genotype were 1-2.5 times greater than the AUC values of the CYP3A5-expressing genotype in a healthy Chinese population. The MDR1 gene encodes P-gp, which is responsible for translocating tacrolimus to the extracellular environment.…”
Section: Correlations Between Indicators and Pharmacokinetic Parametersmentioning
confidence: 64%
“…14 Patients with CYP3A5-expressing genotypes require 1.5 to 2 times the dose of tacrolimus to achieve the same blood concentration. [15][16][17][18] The tacrolimus analysis of the subjects in this study who received the same dose showed that the AUC values of the CYP3A5-nonexpressing genotype were 1-2.5 times greater than the AUC values of the CYP3A5-expressing genotype in a healthy Chinese population. The MDR1 gene encodes P-gp, which is responsible for translocating tacrolimus to the extracellular environment.…”
Section: Correlations Between Indicators and Pharmacokinetic Parametersmentioning
confidence: 64%